2019
DOI: 10.1021/acscatal.9b02512
|View full text |Cite
|
Sign up to set email alerts
|

Chameleon-like Behavior of the Directing Group in the Rh(III)-Catalyzed Regioselective C–H Amidation of Indole: An Experimental and Computational Study

Abstract: The Rh­(III)-catalyzed regioselective C–H amidation of N-methoxy-1H-indole-1-carboxamides by 1,4,2-dioxazol-5-ones was studied. N-Methoxy amide, the directing group (DG) of interest, undergoes four different transformations through DG-retained, -coupled, -eliminated, or -migrated processes under moderately varied reaction conditions. Solvents, additives, and temperature play important roles in these selective transformations; a trace addition of water favors the functional group (FG)-assisted DG elimination; e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…To gain more insight into the mechanism of these protocols, several mechanism experiments were conducted. It was found that the stable complex 6 , which can be synthesized smoothly by the previous literature procedure, [6k] could act as an active catalyst intermediate to catalyze the reaction between 1 a and 2 a , affording the expected 3 aa (63%) and 4 aa (79%), respectively. Subsequently, a kinetic isotope effect value of 1.1 was observed, which suggests that the C−H activation events is not involved in the rate‐determining step.…”
Section: Methodsmentioning
confidence: 99%
“…To gain more insight into the mechanism of these protocols, several mechanism experiments were conducted. It was found that the stable complex 6 , which can be synthesized smoothly by the previous literature procedure, [6k] could act as an active catalyst intermediate to catalyze the reaction between 1 a and 2 a , affording the expected 3 aa (63%) and 4 aa (79%), respectively. Subsequently, a kinetic isotope effect value of 1.1 was observed, which suggests that the C−H activation events is not involved in the rate‐determining step.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, the same group reported a Rh(III)‐catalyzed C−H cyclization of N ‐carboxamide indoles and diazonaphthalen‐2(1 H )‐ones to synthesize lactones (Scheme 1b) [14] . More recently, a Rh(III)‐catalyzed regioselective C−H amidation of N ‐carbamoylindoles with 1,4,2‐dioxazol‐5‐ones was reported by Zou and co‐workers (Scheme 1c) [15] …”
Section: Figurementioning
confidence: 99%
“…Recently, the Zou group reported a series of Rh‐catalyzed C−H amination of indole‐ N ‐carboxamides 113 with dioxazol‐5‐ones 114 . This process could selectively obtain four types of products by changing reaction conditions (Scheme ).…”
Section: Indole‐n‐carboxamides In C−h Activationmentioning
confidence: 99%
“…The obtained products could Recently, the Zou group reported a series of Rh-catalyzed CÀ H amination of indole-N-carboxamides 113 with dioxazol-5ones 114. [38] This process could selectively obtain four types of products by changing reaction conditions (Scheme 28). When N-methoxy Indole-N-carboxamides 113 were treated with 5 mol % [Cp*RhCl 2 ] 2, 30 mol % Zn(OTf) 2 and 1 equivalent of NaOAc at ambient temperature in THF, DG-retained products 2acylamino indoles 115 could be formed up to 92% yields.…”
Section: Reaction Of Indole-n-carboxamides With Other Compoundsmentioning
confidence: 99%